Oil palm waste: An abundant and promising feedstock for microwave pyrolysis conversion into good quality biochar with potential multi-applications - Rock, Keey Liew; Wai, Lun Nam; Min, Yee Chong; Xue, Yee Phang; Man, Huan Su; Peter Nai, Yuh Yek; Nyuk, Ling Ma; Cheng, C. K.; Cheng, Tung Chong; Su, Shiung Lam (Elsevier, 2018)
Oil palm waste (OPW), comprising mainly of empty fruit bunch, mesocarp fiber, frond, trunk, and palm kernel shell generated from palm oil industry, was collected, characterized, and then pyrolyzed to evaluate their potential to be converted into biochar with desirable properties for use in multi-applications. The OPW was detected to have considerable amounts of carbon (43–51 wt%) and fixed carbon (30–39 wt%), showing potential to be converted into carbon-rich biochar. Microwave pyrolysis of palm kernel shell as the selected OPW produced a biochar with zero sulphur content and high heating value (23–26 MJ/kg) that is nearly comparable to conventional coal, thus indicating its potential as an eco-friendly solid fuel. The biochar obtained was also showed low moisture (<3 wt%) and ash (3 wt%), and a highly porous structure with high BET surface area (210 m2/g), indicating the presence of many adsorption sites and thus showing desirable characteristics for potential use as pollutant adsorbent in wastewater treatment, or bio-fertilizer to absorb nutrient and promote plant growth. Our results demonstrate that OPW is a biowaste that shows exceptional promise to be transformed into high-grade biochar rather than simply disposed by landfilling or burned as low-grade fuel in boiler.